Politeness in the Comment Section of the YouTube Channel Entertainment News - Syahputra, Bambang Panca; Anggreani, Fyzza; Amri, Yusni Khairul (Journal of English Language and Education, 2024)
YouTube is a popular platform utilized by a diverse range of people for various purposes, such as documentary videos, the latest news, tutorials, and more. As a result, a wide variety of speech styles can be found on the platform, reflecting different levels of politeness. This analysis was conducted to explore politeness in language within the comments section of a specific video. The source for this research is the video titled "The Case of P Diddy" from the Entertainment News YouTube channel. The video has a duration of 7 minutes and 8 seconds and was published on September 27, 2024. The data was analysed using politeness maxims. This study references six politeness maxims according to Leech (1993: 206-219). Employing a qualitative descriptive research method, the results indicate that out of the 80 comments analysed, there were 25 instances of identified maxims: 4 maxims of wisdom, 5 maxims of generosity, 5 maxims of appreciation, 4 maxims of simplicity, 4 maxims of agreement, and 3 maxims of sympathy.